2022
DOI: 10.3390/su142315584
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration–Flotation of Microplastics Using Kerosene as Bridging Liquid for Particle Size Enlargement

Abstract: Microplastics (MPs), defined as plastics with diameters between 1 and 5000 µm, are problematic pollutants in the environment, but their removal is challenging because of their minute size. One promising approach for their removal is flotation because MPs are inherently hydrophobic. However, the very small particle size of MPs lowers the probability of MPs-bubble collision and attachment that in turn affects the efficiency of the process. To address this challenge, we propose the use of agglomeration-flotation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…It was observed that the removal rates for PP, PE, ABS, and PS decreased to 89.6%, 90.6%, 92.8%, and 87.8%, respectively. This decline can be attributed to the excessive dosage of kerosene, which might adhere to the column walls and diminish the floatability of the MPs [17]. Furthermore, both PET and PVC exhibited a significant reduction in their removal rates, decreasing to 77.5% and 77.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the removal rates for PP, PE, ABS, and PS decreased to 89.6%, 90.6%, 92.8%, and 87.8%, respectively. This decline can be attributed to the excessive dosage of kerosene, which might adhere to the column walls and diminish the floatability of the MPs [17]. Furthermore, both PET and PVC exhibited a significant reduction in their removal rates, decreasing to 77.5% and 77.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hornn and co-workers, for example, showed that by combining surfactants, oil and sufficient mixing before flotation, agglomeration of chalcopyrite could be induced that improved copper recovery [ 85 , 281 , 282 ]. Oil-agglomeration of fine particles can also be applied for the quantification and removal hydrophobic microplastics from contaminated soils, sediments, and water [ 283 ]. Lares et al (2019), for example, used canola oil to improve the recovery and measurement of microplastics from wastewater treatment plant sewage sludge [ 284 ].…”
Section: Critical Discussion Future Perspective and Conclusionmentioning
confidence: 99%
“…Despite these issues, it would be a misconception to classify PVC as non-recyclable, 6 especially with the fact that PVC waste sorting 7 and recycling technologies are in constant advancement. Nonetheless, the investigation of chemical recycling methods for PVC is worthwhile to pursue in parallel.…”
Section: Introductionmentioning
confidence: 99%